2003
DOI: 10.1046/j.1440-1843.2003.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IL‐1β, TNF‐α, and macrophage migration inhibitory factor on prostacyclin synthesis in rat pulmonary artery smooth muscle cells

Abstract: These results suggest that TNF-alpha and MIF are potentially antagonistic to the action of PGI2 in rat PASMCs via down-regulation of PGIS mRNA. Simultaneous induction of COX-2 mRNA may further counteract the action of PGI2 by increasing the levels of eicosanoids other than PGI2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 28 publications
1
40
0
1
Order By: Relevance
“…MIF, a critical upstream regulator of inflammation, inhibits prostacyclin synthase expression in animal models of hypoxiainduced pulmonary hypertension and is associated with pulmonary artery smooth-muscle cell proliferation. 24,25 Studies involving other diseases have also shown that MIF can activate aromatase and increase estradiol levels. 26 Additionally, MIF has been implicated in the pathogenesis of several autoimmune diseases, including autoimmune liver disease, [27][28][29][30] which is a known risk factor for POPH.…”
Section: Discussionmentioning
confidence: 99%
“…MIF, a critical upstream regulator of inflammation, inhibits prostacyclin synthase expression in animal models of hypoxiainduced pulmonary hypertension and is associated with pulmonary artery smooth-muscle cell proliferation. 24,25 Studies involving other diseases have also shown that MIF can activate aromatase and increase estradiol levels. 26 Additionally, MIF has been implicated in the pathogenesis of several autoimmune diseases, including autoimmune liver disease, [27][28][29][30] which is a known risk factor for POPH.…”
Section: Discussionmentioning
confidence: 99%
“…Although not specifically tested in these studies, it is likely that PGI 2 exerts its effects primarily by acutely decreasing the secretion of ghrelin from these enteric cells. IL-1b has been previously shown to increase the production of PGI 2 in numerous other tissues, primarily by upregulating the expression and action of COX-2 (Belt et al 1999, Caughey et al 2001, Walch and Morris 2002, Itoh et al 2003. Obviously, one of the outcomes of this acute decrease in circulating ghrelin would be the development of anorexia as is typical of the acute illness response.…”
Section: Discussionmentioning
confidence: 99%
“…[105][106][107]111,112,114,124 Several reports indicate that the pro-inflammatory cytokine tumor necrosis factor alpha (TNF-␣) plays a role in nondiabetic painful neuropathy. [125][126][127] It is quite plausible that it also plays a role in diabetic neuropathic pain (as has been suggested 128,129 ), because TNF-␣ expression is increased in tissues of diabetic animals, and TNF-␣ induces overexpression of cyclooxygenase-2, 130,131 also implicated in diabetic hyperalgesia and allodynia. 97,99 TNF-␣ antagonists have never been tested in models of diabetic painful neuropathy.…”
Section: Strategies For Drug Discoverymentioning
confidence: 95%